Artificial intelligence in the development of Islamic education learning at Pondok Pesantren: a literature review analysis - Izfanna, Duna; Handayani, Dini Oktarina Dwi; Lestari, Tutik (Universitas Darunnajah, Jakarta, Indonesia, 2025)
The rapid advancement of Artificial Intelligence (AI) technology has opened up transformative opportunities across various sectors, including education. However, the adoption of AI in traditional educational institutions such as Islamic boarding schools (pesantren) remains limited. This study aims to explore how AI can be integrated into the pesantren ecosystem to support educational innovation and institutional sustainability. Employing a literature review approach, the research investigates the potential applications of AI in learning systems, administrative management, and decision-making processes within pesantren. The findings reveal that AI can enhance value-based education, accelerate digital transformation, and strengthen the self-reliance of pesantren in the digital era. Furthermore, this study proposes a conceptual framework for AI transformation aligned with the values and specific needs of pesantren. These insights contribute to the development of sustainable, technology-based Islamic education strategies